Meier-Gorlin syndrome with ventriculomegaly and hypoplastic corpus callosum: a rarely reported congenital malformation - Nabanita Kora; Kaustav Nayek; Baisakhi Soren; Rajib Das (Hygeia Press di Corridori Marinella, 2016)
Meier-Gorlin syndrome (MGS) or ear-patella-short stature syndrome (MIM 224690) is a rarely reported autosomal recessive disorder having characteristic triad of microtia, short stature and aplastic or hypoplastic patella. Only 67 cases are reported. We are reporting a newborn female baby with typical features of MGS along with some other features never described before, ventriculomegaly and hypoplastic corpus callosum. We did x-rays of whole body (infantogram) and MRI of brain for microcephaly. Ultrasonography of both knees showed absence of patellae and brain MRI showed ventriculomegaly and hypoplastic corpus callosum. To our best knowledge this is the second case report of MGS in India; the first reported a MGS associated with papilledema. In previously reported cases, there was no statement regarding agenesis of corpus callosum.